The Auliya Meaning and Its Implementation in the Indonesia’s and Malaysia’s Leader Election - Astari, Rika; Mukhlis, Abdul; Faturrahman, Muhammad Irfan; Seman, Mohammad Bin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
The purpose of this study was to describe the understanding of the meaning of the word ‘auliya’ in Quran Al-Maidah:51 and its implementation in the Indonesia and Malaysia leader election. This research was a qualitative study with library analysis where the data were derived from questionnaire and interview of 26 respondents from Indonesia and Malaysia. The respondents were those who understood Arabic and were able to interpret the Quran. The object of the research was the translation of Surah Almaidah verse by JAKIM and the Ministry of Religious Affairs of Indonesia. The Creswell model was used in data analysis by reading, coding, interpreting and giving the meaning to topics. A descriptive statistical analysis was used to describe the data from questionnaire and interview. It was found that Indonesian and Malaysian respondents had a similar perception to understand the meaning of the word ‘auliya’ as a leader implemented in the presidential and governors elections, and even to determine political parties. The difference in the translation of the Quran did not have a significant effect on the political practices in Indonesia and Malaysia